HUBUNGAN KUALITAS KEHIDUPAN KERJA TERHADAP KINERJA PERAWAT PELAKSANA - Amella Gusty; Dachriyanus Dachriyanus; Leni Merdawati (Jurnal Ilmiah Permas: Jurnal Ilmiah STIKES Kendal, 2019)
Adolescence is a period of transition from children to adults, during this time various physical and non-physical developments occur that can increase sexual desire in adolescents. Problem that often occurs in adolescents is sexual behavior. Self-concept can affect a person's behavior including risky sexual behavior. Teenagers with low self-concept are prone to high-risk sexual behavior. This study was descriptive correlative, design with cross sectional approach with aims to know the relationship between self concept with sexual risk behavior in adolescence at one of the high school in Bandung. The population was 449 students, and used stratified random sampling and obtained samples as many as 212 students. This study used two instruments, Tennesse Self Concept Scale questionnaire and sexual risk behavior questionnaire. This study used univariate dan bivariate with spearman rank data analysis. This research was conducted in May 2019 and has received ethical permission from the Ethics Commission of Padjadjaran University with the number 594/UN6.KEP/EC/2019. The results showed that 100% of the respondents have high self concept. Then, 50.5% of respondents behave sexually at high risk. The results of bivariate analysis showed p value <0.05 (0.018) which means there was a correlation between self concept with sexual risk behavior. It is recommended to health service institutions to improve health education regarding risky sexual behavior in adolescents.